Working as a white adult educator, using our own life stories to explore asymmetries of power and privilege. Issue 1 (2nd January 2020) - Fitzsimons, Camilla
Abstract: The article is principally written for adult educators. It models an auto-ethnographic approach situating this within a critical pedagogic orientation. As an adult educator working in the Republic of Ireland, I draw from two instances in my own life that helped me to re-think my racialised identity. By reflecting on discomforts in terms of my own racial identity, the internalised nature of both white supremacy and racial oppression emerge. The stories and reflections that I share are intended as a prompt for other adult educators, particularly white-educators, to think about their own racialised identity and to contemplate ways in which they benefit from often unacknowledged advantages. This awareness can better equip adult educators to problematise simplistic interpretations of multiculturalism and to authentically ally with those who carry the weight of discrimination.